Remembering the Empire: Imperial Nostalgia and Amnesia in 1898: Los últimos de Filipinas (2016) by Salvador Calvo - Swanson, Ross; Hanashiro Ávila, Nae (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
This article analyzes the Spanish film 1898: Los últimos de Filipinas (2016) by director Salvador Calvo, a dramatization of an episode of the Spanish-American War. Several critics have read the film as a nuanced and anti-patriotic adaptation of this historical event, in contrast to the Francoist propaganda film Los últimos de Filipinas (1945) by Antonio Román. Drawing on the term “imperial amnesia”, we argue that the film patriotically highlights the heroism of the Spanish characters while downplaying the violence of the colonial relationship. In the end, this narrative enacts a fantasy of reconciliation between Spain and the Philippines.